2017
DOI: 10.1371/journal.pone.0182634
|View full text |Cite
|
Sign up to set email alerts
|

Shaping visual space perception through bodily sensations: Testing the impact of nociceptive stimuli on visual perception in peripersonal space with temporal order judgments

Abstract: Coordinating spatial perception between body space and its external surrounding space is essential to adapt behaviors to objects, especially when they are noxious. Such coherent multisensory representation of the body extended into external space is conceptualized by the notion of peripersonal reference frame, mapping the portion of space in which somatic and extra-somatic inputs interact closely. Studies on crossmodal interactions between nociception and vision have been scarce. Here we investigated how the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 74 publications
2
33
0
Order By: Relevance
“…Research has shown that although visual stimuli can affect body sensations, spatial stimuli can have a larger effect. The study found that when the visual stimuli was in closer proximity to the participant there was a higher bodily sensation (Filbrich et al, 2017).…”
Section: Bodily Sensationsmentioning
confidence: 91%
“…Research has shown that although visual stimuli can affect body sensations, spatial stimuli can have a larger effect. The study found that when the visual stimuli was in closer proximity to the participant there was a higher bodily sensation (Filbrich et al, 2017).…”
Section: Bodily Sensationsmentioning
confidence: 91%
“…Spatiotopic mapping therefore offers a multimodal reference frame shared by the different sensory modalities. Nociceptive stimuli have been shown to interact with visual stimuli, especially with those occurring in the proximity of the limb on which the nociceptive stimuli are applied (De Paepe et al, 2015, 2017De Paepe et al, 2014;Filbrich, Alamia, Blandiaux, et al, 2017;Filbrich et al, 2018). Accordingly, nociceptive stimuli interact with extra-somatic stimuli in the peripersonal reference frame, a representation integrating spatial information from the body space and spatial information from the external space immediately surrounding the body (Vallar & Maravita, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These biases can be generated by exogenous shifts of attention when lateralized non-target stimuli are presented shortly before the pair of target stimuli (e.g. 29 , 38 , 42 ), but also by endogenous shifts of attention when participants voluntary allocate spatial attention towards a location, either in response to a cue pointing in that direction or due to increased motivation to attend to the location (e.g. 13 , 39 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…We included in our study two TOJ tasks on pairs of vibrotactile stimuli applied onto the sensitized and control arm, and on pairs of visual stimuli flashed on either arm. We used an adaptive TOJ task, which has the advantage of selecting the SOAs between the two stimuli on the basis of the performance of the participant (Bayesian approach), thereby allowing a smaller number of trials 28 , 29 without reducing the precision of the outcome (see 30 ). Participants’ performance was measured immediately before HFS (T0) and twice after HFS, at 20 (T1) and at 45 (T2) minutes after the end of sensitization, in line with the experimental design used in previous studies (e.g.…”
Section: Introductionmentioning
confidence: 99%